The Differences of Serum Metabolites Between Patients With Early-Stage Alzheimer's Disease and Mild Cognitive Impairment - Weng, Wei-Chieh; Huang, Wen-Yi; Tang, Hsiang-Yu; Cheng, Mei-Ling; Chen, Kuan-Hsing (Frontiers in Neurology, 2019)
Background: Mild cognitive impairment (MCI) is regarded as a transition phase between normal aging and Alzheimer’s disease (AD). Identification of novel and noninvasive biomarkers for distinguish AD in early stage from MCI is warranted for therapeutic and support planning. The goal of this study was to identify the differences of serum metabolomic profiles between MCI and early-stage AD, which could be potential noninvasive biomarkers for early diagnosis of AD. Methods: The subjects enrolled in the study were classified into two diagnostic groups: MCI (n=40) and early-stage AD (n=40). Targeted metabolomics analysis of serum samples was performed using the Biocrates Absolute-IDQ P180 Kit. Targeted metabolic data were analyzed by TargetLynx, and MetIDQ software was applied to integrate the metabolites by automated calculation of metabolite concentrations. Results: The datasets of targeted metabolite analysis was analyzed by the orthogonal-projection-to-latent-structure–discriminant-analysis (OPLS-DA) model. The OPLS-DA score plots demonstrated considerable separation between the MCI and early-stage AD patients. The levels of pimelylcarnitine, putrescine, SM (OH) C24:1, and SM C24:0 were significantly lower, whereas the levels of acetylornithine, methionine sulfoxide, and PC ae C44:3 were significantly higher in early-stage AD patients as compared with MCI patients. Receiver operating characteristic curve analysis of combination of three lipid metabolites (SM (OH) C24:1, SM C24:0 and PC ae C44:3) showed an acceptable discrimination between the early-stage AD and MCI patients (area under curve = 0.788). Conclusions: Our results characterized the differences of serum metabolic profiles between MCI and early-stage AD patients. The positive findings from this study indicate that the minimally invasive method of blood sampling may help to identify patients with AD in early stage from those with MCI.